Sądy jako organy wymiaru sprawiedliwości w polskim porządku prawnym - Jaworska, Malwina (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2016)
Entrusting with the exercise of judicial authority to the courts and tribunals in Poland makes them a part of the state apparatus, in whose competence lies protection of freedom and rights of a citizen, what entails the need for securing the established legal order by the units themselves as well as by other public authorities. The objective of this article is to present the key elements of functioning of the courts as authorities whose essential and fundamental duty in the Republic of Poland is administration of justice, thus settlement of the existing legal conflicts. In this scope, the range of cognitions of the Supreme Court, general jurisdiction courts, administrative courts, and military courts has been presented, and it has been accented that the factor of effective functioning of those judicial authorities is establishment of clear boundaries of jurisdiction ratione materiae of each of them, so that the possible competence disputes are limited, on one hand, and do not deprive the person who is seeking the legal protection of the court proceedings, on the other.
Keywords: human rights; courts; right to a fair trial